2010
DOI: 10.1177/1545968310380687
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Inconsistent Step-Length Asymmetries Across Hemiplegic Stroke Patients

Abstract: Background. In hemiplegic gait, step length typically differs in magnitude between paretic and nonparetic sides. However, the direction of step-length asymmetry varies across stroke patients. Objective. The study sought to understand directional variations in step-length asymmetry in terms of asymmetries in forward foot placement relative to the trunk and trunk progression. Methods. A total of 10 hemiplegic stroke patients and 9 healthy elderly controls walked at a self-selected comfortable speed while pelvic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 20 publications
11
88
3
1
Order By: Relevance
“…However, our results show few differences in stepping patterns according to turn direction; a finding that has also been reported in previous studies [5][6][7]. Given that the direction and extent of step asymmetry has been shown to vary according to age, motor recovery level and walking speed [26][27][28], systematic differences in stepping patterns according to the direction of the turn may be obscured by the complexity of relationships between these variables. This is the first report of turning under dual task conditions and so opportunities for like-for-like comparisons with other studies are limited.…”
Section: Discussionsupporting
confidence: 88%
“…However, our results show few differences in stepping patterns according to turn direction; a finding that has also been reported in previous studies [5][6][7]. Given that the direction and extent of step asymmetry has been shown to vary according to age, motor recovery level and walking speed [26][27][28], systematic differences in stepping patterns according to the direction of the turn may be obscured by the complexity of relationships between these variables. This is the first report of turning under dual task conditions and so opportunities for like-for-like comparisons with other studies are limited.…”
Section: Discussionsupporting
confidence: 88%
“…As several biomechanical factors could affect the forward propulsion, the authors quantified the joint moment impulses of the hip, knee, and ankle during late single stance phase and double support phase. Briefly, their results showed that all groups (longer paretic, shorter paretic and equal step length) presented a reduced plantarflexion moment impulse in late single stance and double support phases, which is coherent with the reduced trunk progression during the non-paretic step (when the paretic foot propulses) previously found by Roerdink et al [26]. However, in individuals with longer paretic step, this observed reduction in plantarflexion moment impulse was more important [17].…”
Section: Biomechanical Impairments Underlying Spatial Asymmetrysupporting
confidence: 64%
“…This quantification allows inter-individual, intersegmental, and inter-parameter comparisons. Among various possibilities of SI [14,17,[25][26][27][28][29], current examples are: A value of 0% represents perfect symmetry for these indices except for the second SI sum equation for which a value of 50% represents perfect symmetry. Limitations of some symmetry indices were analyzed in a study by Zifchock et al [24].…”
Section: Symmetry Indices (Si)mentioning
confidence: 99%
See 2 more Smart Citations